JOHN LENNON’S QUEST FOR PEACE IN HIS LYRIC “IMAGINE” - WAWOLUMAYA, FRILEONAL (LANTERN (Journal on English Language, Culture and Literature), 2015)
In this thesis, the writer discusses about John Lennon’s quest for peace in his lyric entitled “Imagine”. The purpose of the study is to find the meaning and to prove the reason that “Imagine” was made for peace. To analyze the lyric, the writer will discuss the lyric as a literary work: poem. The writer uses the library research as the method of the study to find references for the thesis. In the method of approach, the writer uses mimetic to help the theory which is sociology literature. In the intrinsic aspects, the writer chose to discuss it per stanza. By using diction, imagery and symbol to analyze the intrinsic aspects, so it is easier to figure the meaning of the lyric. Based on the analysis, the writer finds that it is true if “Imagine” had many influences in John Lennon’s life background as a peace activist. There are also some parts of the lyric which are related to his social background. John Lennon had the ambition to stop the war, making peace, and helping one and another for a better place for living. He exploited his fame by using the media and used his lyric so the world could hear like “Imagine”. The result of the study shows that “Imagine” was made to response the class system, differences, and people’s ego. John Lennon created “Imagine” for the world to hear and to live in peace. It is proved that in this thesis, “Imagine” was made as John Lennon’s quest for peace.